Immunosuppression in Malaria: Do Plasmodium falciparum Parasites Hijack the Host? - Calle, Carlos Lamsfus; Mordmüller, Benjamin; Singh, Anurag (Pathogens (Basel), 2021)
Malaria reflects not only a state of immune activation, but also a state of general immune defect or immunosuppression, of complex etiology that can last longer than the actual episode. Inhabitants of malaria-endemic regions with lifelong exposure to the parasite show an exhausted or immune regulatory profile compared to non- or minimally exposed subjects. Several studies and experiments to identify and characterize the cause of this malaria-related immunosuppression have shown that malaria suppresses humoral and cellular responses to both homologous (Plasmodium) and heterologous antigens (e.g., vaccines). However, neither the underlying mechanisms nor the relative involvement of different types of immune cells in immunosuppression during malaria is well understood. Moreover, the implication of the parasite during the different stages of the modulation of immunity has not been addressed in detail. There is growing evidence of a role of immune regulators and cellular components in malaria that may lead to immunosuppression that needs further research. In this review, we summarize the current evidence on how malaria parasites may directly and indirectly induce immunosuppression and investigate the potential role of specific cell types, effector molecules and other immunoregulatory factors.